Vinnikova N. Ukrainian literary parody in the magazines of the 40-50-th years XX century - Vinnikova N. (Philological Treatises, 2020)
This article deals with the Ukrainian literary parodies which were printed on the pages of magazines in the 40-50th last century. Objects, artistic facilities and receptions of the parodying are characterized. The parodies’ level, their accordance to parody genre are analysed.